Lifetime Controlling Defects in Tool Steels - Sohar, Christian Rudolf; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
In this thesis Christian Sohar describes his investigation into the gigacycle fatigue behavior of tool steels. In an interdisciplinary approach he uses knowledge and methods from a wide variety of disciplines including materials science, metallurgy, chemistry, physics and mechanical engineering. Christian gives a general introduction into steel tools and fatigue in materials. Later he extensively discusses the experimental techniques and results. Indeed it is the detail of the content in this thesis which makes it an invaluable resource for students entering the field and scientists working in related disciplines. Overall, the thesis helps us understand more about the mechanical behavior of metallic materials with complex microstructure and high hardness.
Introduction -- Experimental -- Results and Discussion -- Summary and Outlook -- List of Figures -- List of Tables -- References.
Keywords: Chemical engineering; Metals; Mechanical engineering; Industrial Chemistry/Chemical Engineering; Metallic Materials; Mechanical Engineering